Memorandum of understanding between Universiti Teknologi MARA and GITAM (deemed to be university), Hyderabad, India / Fakulti Farmasi - Universiti Teknologi MARA, Fakulti Farmasi (Universiti Teknologi MARA (UiTM), 2019)
This agreement is attached to and a part of the MoU between UiTM and GITAM Deemed to be University. Both institutions shall, on the basis of reciprocity, support and promote spirit of this agreement to encourage academic collaboration and to facilitate as much as possible the academic progress.